Using Game Theory for a Schumpeterian analysis of emerging industries: the historical case of the U.S. Steel industry - Maurer, Florian; Fritzsche, Albrecht (Journal of Management History, 2024)
Purpose This paper aims to explore the development of the US steel industry from the 19th to the 20th century by applying the Schumpeterian perspective on the concept of creative destruction. It introduces Game Theory as a means to describe patterns of strategic situations and entrepreneurial decision-making in an emerging industry. Design/methodology/approach Based on a narrative literature review of Schumpeter’s concept of creative destruction, four historical case studies have been designed. These historical case studies build the basis for game-theoretically analysis and evaluation. In doing so, the authors identify games with different payoff matrices that take place while an industry emerges, reflecting different layers of creative destruction. Findings Emerging industries, as this paper highlights, go through several stages of development until they reach full maturity. With Schumpeter, these stages can be studied through an entrepreneurial lens, highlighting different patterns of decision-making in each respective stage. This paper adds to a better understanding of emerging industries. Furthermore, this paper provides a methodological repertoire that can also be applied to other cases as well, such as the emergence of contemporary digital industries. Research limitations/implications The paper provides a horizontal overview of how Game Theory can be applied to analyze industrial epochs and how the concept of creative destruction works in industry and transforms industry. It introduces Game Theory to management and business history as a sound methodological base to analyze and evaluate strategic situations and entrepreneurial decision-making. Practical implications The paper presents a comprehensive method to act in the different stages of an industrial epoch and how to act. The games applied in the particular layers of creative destruction give an insight into the analysis of strategic situations and strategic decision-making in the industry. Originality/value This paper provides a horizontal perspective on strategic games that can be used as an analysis methodology in the field of entrepreneurship and applied in contemporary industries. It connects historical cases out of the US steel industry with Schumpeter’s concept of creative destruction and Game Theor
Keywords: Creative destruction; Game Theory; Business Cycles; Industry evolution; Dynamic entrepeneur